(untitled) (PerCursos, 2021)
To contribute to the debate on decolonization from the perspective of Indigenous Peoples, we present the notion of Resurgence elaborated by Taiaiake Alfred, one of Canada’s most important Indigenous thinkers. Alfred proposes his notion of Resurgence as a strategy for breaking away from colonial power relations that focus on Indigenous Peoples’ ability to live and develop according to their own thinking systems. We will see that, besides questioning colonial domination, the notion of Resurgence, anchored in the millenary experiences and wisdom of Indigenous Peoples, shows how to prepare the way and create the necessary conditions for a true decolonization.